A study of the star-forming regions in the spiral galaxy NGC 2336 using the Ultraviolet Imaging Telescope (UVIT). Issue 1 (17th August 2018) - Rahna, P T; Das, M; Murthy, Jayant; Gudennavar, S B; Bubbly, S G
ABSTRACT: We present a far-ultraviolet (FUV) and near-ultraviolet (NUV) imaging study at 1.2 arcsec resolution of recent star formation in the nearby spiral galaxy NGC 2336 using the Ultraviolet Imaging Telescope (UVIT) on-board AstroSat . NGC 2336 is nearly face-on in orientation and has a multi-armed, branching spiral structure which is associated with star-forming regions distributed mainly along the spiral arms and in the co-rotation ring around the bar. We have identified 78 star-forming complexes in the disc, of which only two are in the interarm regions and six in the co-rotation ring. We have determined their positions and estimated their luminosities, sizes, star formation rates (SFRs), colours, and ages. The median size of the star-forming complexes is 389 pc in NUV and 448 pc in FUV. The SFRs vary from 2.6 × 10 −4 to 5.5 × 10 −2 M⊙  yr −1 in NUV and from 2 × 10 −4 to 3.1 × 10 −2 M⊙  yr −1 in FUV. The central region of the galaxy is dominated by NUV emission while the outer disc is dominated by FUV. We found that the star formation is driven by the spiral density wave in the galaxy disc and is best traced by UV imaging which encompasses clusters spanning a wide range of star-forming ages and sizes.